Optimization of synthesis of fatty acid methyl esters catalyzed by lipase B from Candida antarctica immobilized on hydrophobic supports - Poppe, Jakeline K.; García-Galán, Cristina; Matte, Carla R.; Fernández-Lafuente, Roberto; Rodrigues, Rafael C.; Ayub, Marco A. Z. (Journal of Molecular Catalysis B: Enzymatic, 2013)
In this work two immobilized preparations of lipase (EC 3.1.1.3) B from Candida antarctica (CALB) were compared for the synthesis of fatty acid methyl esters (FAME) using soybean oil. Commercial Novozym 435 (CALB-435) and CALB immobilized on styrene-divinylbenzene beads (CALB–MCI) were tested for the transesterification reactions. Central composite design (CCD) and response surface methodology (RSM) were used to optimize the reaction parameters, substrate molar ratio, enzyme content, and the added amount of water, on the initial reaction rate as response. The biocatalysts showed different optimal conditions for the production of FAME. For CALB-435, optima conditions were 5.6:1 molar ratio methanol:oil, 25% enzyme, and 5.44% of added water, while for MCI–CALB, these optima were 3:1 molar ratio methanol:oil, 25% enzyme, and 1.18% of added water, resulting in initial reaction rates of 51.47 mmol L−1 h−1, and 57 mmol L−1 h−1 of FAME, respectively. Conversions of 93.38% using CALB-435, and 99.03% using CALB–MCI were obtained after 72 h of reaction under the optimized conditions. Repeated batches of reaction were carried out to test the operational stability of biocatalysts, with both preparations keeping around 70% of their initial activity after eight batches. This work was supported by grants from Brazilian Coordenação de Aperfoiçoamento de Pessoal de Nível Superior (CAPES) and CTQ2009-07568 from Spanish Ministerio de Ciencia e Innovación. Peer Reviewed